Molecular mechanisms associated with Fluconazole resistance in clinical Candida albicans isolates from India. Issue 2 (9th December 2015) - Mane, Arati; Vidhate, Pallavi; Kusro, Chanchal; Waman, Vaishali; Saxena, Vandana; Kulkarni‐Kale, Urmila; Risbud, Arun
Summary: Resistance to azole antifungals is a significant problem in Candida albicans . An understanding of resistance at molecular level is essential for the development of strategies to tackle resistance and rationale design of newer antifungals and target‐based molecular approaches. This study presents the first evaluation of molecular mechanisms associated with fluconazole resistance in clinical C.albicans isolates from India. Target site ( ERG11 ) alterations were determined by DNA sequencing, whereas real‐time PCRs were performed to quantify target and efflux pump genes ( CDR1, CDR2, MDR1) in 87 [Fluconazole susceptible ( n = 30), susceptible‐dose dependent ( n = 30) and resistant ( n = 27)] C.albicans isolates. Cross‐resistance to fluconazole, ketoconazole and itraconazole was observed in 74.1% isolates. Six amino acid substitutions were identified, including 4 (E116D, F145L, E226D, I437V) previously reported ones and 2 (P406L, Q474H) new ones. CDR1 over‐expression was seen in 77.7% resistant isolates. CDR2 was exclusively expressed with CDR1 and their concomitant over‐expression was associated with azole cross‐resistance. MDR1 and ERG11 over‐expression did not seem to be associated with resistance. Our results show that drug efflux mediated by Adenosine‐5′‐triphosphate (ATP)‐binding cassette transporters, especially CDR1 is the predominant mechanism of fluconazole resistance and azole cross‐resistance in C. albicans and indicate the need for research directed towards developing strategies to tackle efflux mediated resistance to salvage azoles.